The production of galacturonic acid enriched fractions and their functionality - Gerschenson, Lia Noemi (2017)
Vegetable tissues discarded at harvesting or after industrial processing constitute a valuable and renewable source of biopolymers and bioactive compounds. Upgrading of vegetable waste can not only reduce pollution but also add value to the commodity production. Plant cell walls are an important source of galacturonic acid compounds The present paper reviews some selected bibliography published in the last years concerning the production of pectin and oligosaccharides based on galacturonic acid, and their functionality with special reference to their effect on health. In relation to pectin it can be concluded that, in addition to their ability to thicken and form gels, they are soluble dietary fibers. They can also act as prebiotics, but more systematic studies must be performed to elucidate the effect of their chemical structure on health. With respect to pectic oligosaccharides rich in galacturonic acid, they have been proposed as prebiotics and immunity enhancers, but the absence of standardized techniques for their production and purification, the ample variety of substrates involved and the lack of systematic studies about their structure does not allow to conclude nowadays about the structure-function relationship and it is a must to deepen these studies to help to the rational usage of oligosaccharides in functional foods.